Question
upstudy study bank question image url

Solve for \( u \). \[ 3+\frac{1}{u+6}=-\frac{5}{(u+1)(u+6)} \] If there is more than one solution, separate them with If there is no solution, click on "No solution".

Ask by Long Macdonald. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( u = -\frac{4}{3} \)

Solution

We are given the equation   3 + 1/(u + 6) = -5/[(u + 1)(u + 6)]. Step 1. Note the restrictions on u. Since u + 6 and u + 1 are in the denominators, we must have   u ≠ -6 and u ≠ -1. Step 2. Multiply both sides of the equation by (u + 1)(u + 6) to eliminate the fractions:   (u + 1)(u + 6)[3 + 1/(u + 6)] = (u + 1)(u + 6)[-5/((u + 1)(u + 6))]. This simplifies to:   3(u + 1)(u + 6) + (u + 1) = -5. Step 3. Factor out (u + 1) from the left-hand side:   (u + 1)[3(u + 6) + 1] = -5. Simplify inside the brackets:   3(u + 6) + 1 = 3u + 18 + 1 = 3u + 19. Thus, the equation becomes:   (u + 1)(3u + 19) = -5. Step 4. Expand the left-hand side:   3u² + 19u + 3u + 19 = 3u² + 22u + 19. Now set the equation equal to zero by adding 5 to both sides:   3u² + 22u + 19 + 5 = 3u² + 22u + 24 = 0. Step 5. Solve the quadratic equation:   3u² + 22u + 24 = 0. We use the quadratic formula, where a = 3, b = 22, and c = 24:   u = [ -22 ± √(22² - 4·3·24) ] / (2·3). Calculate the discriminant:   22² - 4·3·24 = 484 - 288 = 196. Since √196 = 14, we have:   u = [ -22 ± 14 ] / 6. This gives two possible solutions: • u = ( -22 + 14 ) / 6 = (-8)/6 = -4/3. • u = ( -22 - 14 ) / 6 = (-36)/6 = -6. Step 6. Check the solutions against the domain restrictions. Since u cannot equal -6 (because it makes the denominator u + 6 equal to zero), we must discard u = -6. Thus, the only valid solution is:   u = -4/3. Answer: -4/3

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve for \( u \) in the equation \[ 3+\frac{1}{u+6}=-\frac{5}{(u+1)(u+6)}, \] first, let's eliminate fractions by multiplying through by \((u+1)(u+6)\): \[ 3(u+1)(u+6) + (u+1) = -5. \] Expanding both sides: \[ 3(u^2 + 7u + 6) + u + 1 = -5. \] This simplifies to: \[ 3u^2 + 21u + 18 + u + 1 = -5. \] Combine like terms: \[ 3u^2 + 22u + 19 = -5. \] Now, add 5 to both sides: \[ 3u^2 + 22u + 24 = 0. \] Next, we can apply the quadratic formula where \( a = 3 \), \( b = 22 \), and \( c = 24 \): \[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{-22 \pm \sqrt{22^2 - 4 \cdot 3 \cdot 24}}{2 \cdot 3}. \] Calculating the discriminant: \[ 22^2 - 4 \cdot 3 \cdot 24 = 484 - 288 = 196. \] Since the discriminant is positive, we have two real solutions. Now plugging this back into the quadratic formula: \[ u = \frac{-22 \pm \sqrt{196}}{6} = \frac{-22 \pm 14}{6}. \] This gives us two possible values for \( u \): 1. \( u_1 = \frac{-22 + 14}{6} = \frac{-8}{6} = -\frac{4}{3} \), 2. \( u_2 = \frac{-22 - 14}{6} = \frac{-36}{6} = -6 \). Thus, the solutions for \( u \) are: \[ -\frac{4}{3}, -6. \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy